Analisis Implementasi Metode Menggambar Bagi Pembentukan Kreativitas Anak Usia Dini Dalam Perspektif Teori Konstruktivisme - Wuri Hartanti; Nur Kholik Afandi (UIN Sultan Maulana Hasanudin Banten, 2023)
Early childhood plays by involving the five senses. Involvement of the five senses will maximize child development. This research will discuss developing children's creativity using the drawing method, because it is obtained from observations in the field that children's drawing creativity is low. This study uses a qualitative research approach. In this study, the results showed that 14 children had different ideas, children used various media, there were crayons, markers and a combination of crayons and markers. Children tell pictures by 3 children mentioning pictures, and 11 children telling stories about the contents of the pictures according to their imagination. The stages of drawing children are in the range of 10-12. In this study it can be concluded that the drawing method can be used to shape children's creativity and in accordance with the perspective of constructivism theory. It is better to apply the drawing method according to the interests of the child, this will be easy for creative ideas to emerge and the child will feel comfortable expressing his ideas.